Journey towards QAA (Quality Assurance and Accreditation) mechanism to improve quality education of HELs (Higher Education Institutions) in Bangladesh - issues, challenges and prospects. - Islam, Gazi Md. Narul (BRAC University, 2015)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2014.